Poly(N-vinyl caprolactam) thermoresponsive polymer in novel drug delivery systems: A review - Marwah Noori, Mohammed; Kamal, Yusoh; Jun Haslinda, Shariffuddin (American Scientific Publishers, 2018)
Thermoresponsive polymers have been attractively and scientifically significant in the recent years due to the utilization of various pharmaceutical and biomedical formulations. Poly(N-vinylcaprolactam) (PNVCL) is a temperature-responsive polymer, only second to poly(N-isopropylacrylamide) (PNIPAM), the most popular temperature-responsive polymer. PNVCL should be considered an important focus due to the phase transition temperature of such polymer that is close to the physiological temperature. PNVCL is a polymer which offers unrivaled qualities for different potential medical device applications. Specifically, it offers one kind of thermoresponsive abilities, which satisfies the material innovation imperatives required in focused drug delivery applications. PNVCL and PNIPAM polymers are well-studied thermoresponsive abilities since its lower critical solution temperature (LCST) is near the physiological temperature and has mostly been used in biomedical applications. Therefore, it can be investigated as a potential candidate for pharmaceutical utilization. This review highlights a comparison of PNVCL with PNIPAM regarding comparable characteristics which also delve into selected examples and the most recent published of applications based on PNVCL with a specific focus on drug delivery system. The consequence exhibits that the PNVCL will play a pivotal role in nanotechnology and the environment.